\(\frac{2n+15}{n+1}=\frac{2n+2+13}{n+1}=\frac{2\left(n+1\right)+13}{n+1}=\frac{2\left(n+1\right)}{n+1}+\frac{13}{n+1}=2+\frac{13}{n+1}\)
Để \(\frac{2n+15}{n+1}\in Z\) <=> \(n+1\inƯ\left(13\right)=\left\{\pm1;\pm13\right\}\)
n + 1 | 1 | -1 | 13 | -13 |
n | 0 | -2 | 12 | -14 |
Vậy để \(\frac{2n+15}{n+1}\in Z\) thì n = {0;-2;12;-14}
\(\frac{2n+15}{n+1}\in Z\Leftrightarrow2n+15⋮n+1\Leftrightarrow2n+2+13⋮n+1\Leftrightarrow2\left(n+1\right)+13⋮n+1\)\(\Leftrightarrow13⋮n+1\) \(\left(vì2\left(n+1\right)⋮n+1\right)\)
\(\Leftrightarrow n+1\inƯ\left(13\right)\Leftrightarrow n+1\in\left\{\pm1;\pm13\right\}\Leftrightarrow n\in\left\{0;-2;12;-14\right\}\)
Vậy\(n\in\left\{0;-2;12;-14\right\}\)